Observations on the Theory of "Movement." - McGee, Michael C. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The purpose of this essay is to examine philosophy, history, sociology, and rhetoric with an eye toward demonstrating that the rhetorician is at least as well equipped to deal with the concept "movement" as other writers with different training. Rhetoricians have been preoccupied with moving men and not societies. A "macrorhetoric," in other words, seems possible by abstracting to a social or cultural level the traditional principles and operations of audience-oriented "microrhetoric." There is no difficulty in deciding what moves in society and history--arguments move. Rhetoricians also are symbolists and thus can beg the ethical problem of determining what progress really is or ought to be. Speculations about movement can be documented, giving rhetoricians a clear indication of which documents produced by which advocates seem to be most important in terms of producing or accomodating social and historical movement. Rhetoricians should not be bothered by problems of meaning; the rhetorician studies events in the past only as they have already been mediated by advocates--politicians, statesmen, and other historical figures--who had the power to legislate a movement in society with the arguments they made. (RB)
ERIC Note: Paper presented at the Annual Meeting of the Speech Communication Association (61st, Houston, December 27-30, 1975).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Analytical Criticism; Cultural Background; Higher Education; History; Persuasive Discourse; Rhetoric; Rhetorical Criticism; Sociocultural Patterns; Theories; Movement Theory; Speeches/Meeting Papers